Establishment of taxonomic status of Macrobrachium indicum Jayachandran & Joseph (Decapoda : Palaemonidae) through molecular characterization with a note on related species - Mary, Ajina S.; Jayachandran, K.v.; Landge, Asha T.; Gladston, Y.; Pavan-Kumar, A. (Zootaxa, 2019)
Macrobrachium indicum, a south Indian freshwater prawn described from Vellayani lake, Kerala is closely related to Koua river prawn, M. australe which in turn resembles M. ustulatum. Morphologically the three species pose difficulties in identification. A comparison of morphological characters of M. indicum, M. australe and M. ustulatum has been made in the paper. The COI sequence data for the species has been generated and made comparison with the existing COI barcode sequences for M. australe and showed clear difference between the species, thereby established the taxonomic validity of the species. Alignment of the present study sequences with reported sequences of M. australe revealed homologous region of 434 bp. Out of 434 nucleotides, the number of conserved and variable nucleotides were 313 and 121, respectively. Based on the P value (0.002) of Mann-Whitney U test, it was observed that the GC content at codon third base position between M. indicum and M. australe is significantly different. Because of the complexity of the species group a type material is highly necessary for confirmation in future studies and since holotype is irrecoverably lost, a neotype has been selected from the present collection and deposited in the CMFRI Museum at Kochi, Kerala with accession number: ED.2.2.1.8.